1996
DOI: 10.1103/physrevb.54.14396
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of the graphite 1sx-ray absorption edges

Abstract: Theoretical calculations in combination with experiments for the * and * x-ray absorption edges are reported for graphite. Theory and experiment agree well for the leading * and * resonances. By comparing theoretical calculations for a single graphene layer that include the effect of the core hole to similar calculations that do not, we find that 1s x-ray absorption in graphite is to be associated with an excitonic effect. Both the * and * excitons are localized primarily on the core-excited atom, but have sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 69 publications
5
60
1
Order By: Relevance
“…Amorphous carbon has been distinguished from highly-ordered graphite as a progressive decrease of the π* exciton (at 285.4 eV), with the appearance of several π* states of similar intensity due to the increase in the sp 2 -related π* states in the region between 285 to 288 eV (Gago et al 2000(Gago et al , 2001. The decrease in the π* exciton is apparently due to the reduction of graphite domain size in the amorphisation process, as theoretical modeling of the XANES spectra found a dependence of the exciton intensity with plane-cluster size (Ahuja et al 1996). The decrease of the π* intensity as the ordered graphite becomes progressively amorphous was likely due to the increase of sp 3 hybridized sites at the expense of the sp 2 hybridized sites.…”
Section: Discussionmentioning
confidence: 90%
“…Amorphous carbon has been distinguished from highly-ordered graphite as a progressive decrease of the π* exciton (at 285.4 eV), with the appearance of several π* states of similar intensity due to the increase in the sp 2 -related π* states in the region between 285 to 288 eV (Gago et al 2000(Gago et al , 2001. The decrease in the π* exciton is apparently due to the reduction of graphite domain size in the amorphisation process, as theoretical modeling of the XANES spectra found a dependence of the exciton intensity with plane-cluster size (Ahuja et al 1996). The decrease of the π* intensity as the ordered graphite becomes progressively amorphous was likely due to the increase of sp 3 hybridized sites at the expense of the sp 2 hybridized sites.…”
Section: Discussionmentioning
confidence: 90%
“…Given this peculiarity, methods within solid state spectroscopy have been developed towards the evaluation of these properties. In this context, for many years carbon based structures have been widely studied by X-ray absorption spectroscopy (XAS), which is a very useful bulk probing method that allows one to both examine the unoccupied density of states and identify different site selective bonding environments (see figure 1) [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the electronic structure of graphite has been widely studied experimentally and theoretically and the σ * and π * thresholds have been examined by various authors [4,5,12,13]. Theoretically, an intense debate existed around a discrepancy of the position of a peak appearing 3 eV above the Fermi level (ε F ) in the ground state density of states (DOS), whereas experimental XAS observations found that peak shifted to only 1 eV above the C1s onset.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral features observed in the regions 283 − 289 eV and 289 − 315 eV are ascribed to C 1s → π * and C 1s → σ * transitions, respectively. The shape of XAS lines in both absorption regions is influenced by considerable excitonic effects through poor core-hole screening [18][19][20]. In the case of the graphene/Ni(111) system, the XAS C 1s → π * , σ * spectrum shows considerable changes compared with the graphite spectrum, indicating a strong chemisorption.…”
mentioning
confidence: 99%